Inactivation of Wnt signaling by a human antibody that recognizes the heparan sulfate chains of glypican-3 for liver cancer therapy - Gao, Wei (2014)
Wnt signaling is important for cancer pathogenesis and is often upregulated in hepatocellular carcinoma (HCC). Heparan sulfate proteoglycans (HSPGs) function as co-receptors or modulators of Wnt activation. Glypican-3 (GPC3) is a HSPG that is highly expressed in HCC, where it can attract Wnt proteins to the cell surface and promote cell proliferation. Thus, GPC3 has emerged as a candidate therapeutic target in liver cancer. While monoclonal antibodies to GPC3 are currently being evaluated in preclinical and clinical studies, none have shown an effect on Wnt signaling. Here, we first document the expression of Wnt3a, multiple Wnt receptors and GPC3 in several HCC cell lines, and demonstrate that GPC3 enhanced the activity of Wnt3a/β-catenin signaling in these cells. Then, we report the identification of HS20, a human monoclonal antibody against GPC3, which preferentially recognized the heparan sulfate chains of GPC3, both the sulfated and non-sulfated portions. HS20 disrupted the interaction of Wnt3a and GPC3 and blocked Wnt3a/β-catenin signaling. Moreover, HS20 inhibited Wnt3a-dependent cell proliferation in vitro and HCC xenograft growth in nude mice. In addition, HS20 had no detectable undesired toxicity in mice. Taken together, our results show that a monoclonal antibody primarily targeting the heparin sulfate chains of GPC3 inhibited Wnt/β-catenin signaling in HCC cells and had potent anti-tumor activity in vivo. CONCLUSION: Here, we provide one of the first examples of an antibody directed against the heparan sulfate of a proteoglycan that showed efficacy in blocking Wnt signaling and HCC growth, suggesting a novel strategy for liver cancer therapy.